Current Views on the Development of the Tympanal Segment of the Facial Nerve - Bakhramdjanovich, Gulyamov Sherzod (Journal of Science in Medicine and Life, 2024)
Ear canal atresia is a congenital or acquired obliteration of the bony cartilaginous canal that connects the auricle to the middle ear. Closure of the auditory canal is accompanied by a decrease in hearing acuity up to deafness. Congenital atresia is often combined with microtia and other developmental anomalies. Diagnosis includes examination by an otolaryngologist with otoscopy, audiometry and computed tomography of the temporal bone. In case of bony overgrowths, skull radiography is performed. Treatment of pathology is surgical. During surgery, an artificial canal is formed using skin and cartilage flaps; if necessary, tympanoplasty is performed. Anomalies of the auricle require plastic reconstructive surgery.